Third Homology of some Sporadic Finite Groups - Johnson-Freyd, T.; Treumann, D. (Symmetry, Integrability and Geometry: Methods and Applications, 2019)
We compute the integral third homology of most of the sporadic finite simple groups and of their central extensions.